Analyzing the Influence of Business Environment on Performance of ICT Firms in Nigeria: Array - Ogunmuyiwa, Michael Segun (Acta Universitatis Danubius. Œconomica, 2022)
The study investigated the influence of business environment on the performance of ICT firms in Lagos State, Nigeria. Survey research design and purposive sampling technique were employed to select a sample of 156 from a total population of 257 employees drawn from Zinox Technologies and Spectranet Nigeria Limited. Data was collected through a 5-point Likert rating questionnaire administered to the selected ICT firms. Empirical findings from the O.L.S regression technique revealed that all the explanatory variables (infrastructural environment, insecurity and political environment) are the critical variables determining fluctuations in ICT performance in Nigeria. Albeit, the coefficient of insecurity was not in conformity with the a-priori expectation, but it was significant at the 5 percent level. Hence, ICT and other allied firms should be cognizant of the business environmental variables particularly insecurity because of its stronger influence on the performance of ICT firms in Nigeria. Government at all levels should provide enabling infrastructural and political environment to improve performance and growth of ICT firms in Nigeria.